Femur finite element model instantiation from partial anatomies using statistical shape and appearance models - Nolte, Daniel; Bull, Anthony M.J. (Medical engineering & physics, 2019)
•Mechanical and geometric properties important for orthopaedic reconstruction.•Statistical shape models allow reconstruction of healthy state.•Reconstructions geometrically comparable to contralateral side.•Differences in stress and strain in similar range as contralateral side. Accurate models of bone shapes are essential for orthopaedic reconstructions. The commonly used methods of using the contralateral side requires an intact bone and anatomical symmetry. Recent studies have shown that statistical shape and appearance models (SSAMs) as an alternative can predict accurate geometric models, but the accuracy of the mechanical property prediction is typically not addressed. This study compares stress and strain differences under identical loading conditions for reconstructions from partial anatomies. SSAMs representing shape and grey values were created using 40 female cadaveric X-ray computed tomography scans. Finite element models were created for shape reconstructions from partial bone of various lengths with boundary conditions obtained from musculoskeletal simulations. Commonly used anatomical measures, measures of the surface deviations and maximal stresses and strains were used to compare the reconstruction accuracy to the contralateral side. Surface errors were smaller compared to the contralateral side for reconstructions with 90% of the bone and slightly bigger when less bone was available. Anatomical measures were comparable. The contralateral side showed slightly smaller relative errors for strains of up to 6% on average. This study has shown that SSAM reconstructions using partial bone geometry are a possible alternative to the contralateral side.